Restitution of nazie confiscated property in the Western Europe after Second world war - Liekis, Šarūnas (Genocidas ir rezistencija, 2002)
Many Lithuanian citizens and politicians alike argue that Western European countries have consistently sought to restore justice and make reparations to the victims of the Holocaust and Nazism since the Second World War. These determined efforts culminated in the triumph of justice and the resolution of all problems. Meanwhile, in the post–communist countries, the process of restitution is in its infancy and is very difficult because it is linked to the individual and collective responsibility of nations. However, it is a complex and long-term process of decades of restitution in Western Europe, but also of expropriation of property, methods, and terms. The situation was different in Eastern and Western Europe. The main similarities between East and West relate to the methods of expropriation, while the differences relate to political and economic factors.
Keywords: German occupation; Holocaust; Jews; compensation; Western Europe